Exploring the Relationship between CLIL and L1 Ability in Finland : Analyzing Written and Oral Production - Launonen, Peter; Roiha, Anssi; Maijala, Minna (Universidad de la Sabana, 2025)
This study explores the relationship between CLIL and L1 ability in a Finnish secondary education context. The study is based on the analysis of L1 written and oral productions of four ninth-grade students (2 CLIL and 2 non-CLIL). Written production was evaluated through a short essay task, while oral production was assessed via a verbal fluency task and a picture naming task. In the written task, students responded to a question related to a topic previously covered in their curriculum. In the verbal fluency task, participants were given 60 seconds to produce as many words as they could beginning with a given letter. In the picture naming task, participants were asked to name 12 pictures that were shown on a screen. The results were analyzed and discussed regarding not only participants’ linguistic backgrounds but also their self-assessed language abilities in English and Finnish. In two of the tasks, the CLIL students performed worse than the non-CLIL students in their L1; however, no clear pattern emerged in the third task. The study sheds light on the relationship between CLIL and L1 ability in the context of a discussion about the benefits and linguistic costs associated with bilingualism. The results highlight the importance of accounting for the impact of socioeconomic status and other L2 exposure in future studies in this area. In addition, the authors contend this is an area of research that merits additional attention given the present and future scope of bilingual education globally.